Evaluating the impact of public health oriented drug law reform on HIV incidence among people who inject drugs in Tijuana, Mexico: an epidemic modelling analysis - Borquez,A; Beletsky,L; Nosyk,B; Strathdee,S; Madrazo,A; Abramovitz,D; RAfful,C; Morales,M; Cepeda,J; Panagiotoglou,D; Krebs,E; Vickerman,P; et al. (Lancet, 2018)
Background: As countries embark on public health-oriented drug law reform, health impact evaluations are needed. In 2012, Mexico mandated the ‘Narcomenudeo reform’, depenalising possession of small amounts of drugs and instituting drug treatment instead of incarceration. We investigated its impact on HIV incidence among people who iinject drugs (PWID) in Tijuana, Mexico.Methods: We developed a deterministic model of injecting and sexual HIV transmission among PWID in Tijuana disaggregated by sex, incarceration status, syringe confiscation by the police, and exposure to drug treatment/”rehabilitation” (either opioid agonist therapy (OAT) or compulsory drug abstinence programmes (CAP)). We modelled the effect of these exposures on HIV risk among PWID, estimating the impact of observed and potential future reform enforcement levels. Findings: Modelling estimated the limited reform implementation averted 2% [95% Confidence Interval (CI): 0.2-15 3%] of new HIV infections among PWID between 2012-2017. If implementation reduced incarceration among PWID by 80% from 2018 onward, 9% [95% CI: 4-16%] of new HIV infections between 2018-2030 could be averted, with 21% [95% CI: 1033%] averted if PWID were referred to OAT instead of incarcerated. However, referral to CAP instead of prison could have a lower or potentially negative impact with -2% [95% CI: 239%] infections averted. Interpretation Mexican drug law reform has had negligible impact on the HIV epidemic among PWID in Tijuana.